Pemberdayaan Keluarga Dalam Melatih Stimulasi Otak dan Ketajaman Penglihatan Menggunakan Fun Thinkers - Cahyaningsih, Oktaviani; Rochmayani, Dewi Sari (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Visual impairment, especially in children, is currently very under-appreciated. A poor learning environment is one of the triggers for decreased visual acuity in children, even though good vision is very important in the teaching and learning process. Training fine motor skills can not only be done at school. but it is most effective if it can be started in the family so that family support is needed to increase brain stimulation and improve visual acuity in addition to good nutritional intake in children. Based on a preliminary survey, there are around 85 toddlers in RW I, Palebon Village, Pedurungan District, where on average, based on information from the parents of each child, they have been introduced to gadgets since the age of 9 months. This is what we need to be aware of regarding eye health problems in toddlers from an early age due to the influence of gadgets. Increasing brain stimulation and improving visual acuity can be done early on through family empowerment, which is something that is not yet widely realized by families in RW I, Palebon, Pedurungan. For the smooth running of family empowerment efforts in training brain stimulation and visual acuity using educational games for pre-school children, there are several categories in the implementation, namely Lectures on the importance of maintaining visual acuity, Practice using Fun Thinker, Role Play, Case Studies and discussions, Evaluation and mentoring with the target being the family. The result of the implementation of this PKM is an increase in family knowledge and skills in training brain stimulation which also has an impact on visual acuity. In realizing that the family plays an important role in training brain stimulation which also has an impact on visual acuity, there needs to be positive activities built in the family, especially those that are useful in increasing brain intelligence by conducting brain stimulation and visual acuity.